Bacillus velezensis EEAM 10B Strengthens Nutrient Metabolic Process in Black Soldier Fly Larvae (Hermetia illucens) via Changing Gut Microbiome and Metabolic Pathways - Pei, Yaxin; Zhao, Sijie; Chen, Xiang; Zhang, Jiran; Ni, Hongyuhang; Sun, Mengxiao; Lin, Hui; Liu, Xinyu; Chen, Hongge; Yang, Sen (Frontiers in Nutrition, 2022)
Insect is a potential alternative protein source to solve the food shortage crisis. Previous researches have illustrated that probiotics can improve substrates conversion efficiency of insect and increase insect protein content. However, the effects of probiotics on insect physiology and nutrient metabolism are still not well understood. Here, the black soldier fly larvae (BSFL), Hermetia illucens (Diptera: Stratiomyidae) was used as a study subject to deeply investigate the specific interaction among a novel probiotic, Bacillus velezensis EEAM 10B (10B), intestinal microbiota, and the host. In this study, the effects of 10B on the survival and physiology of BSFL were first analyzed. It shows that 10B significantly elevated the substrate conversion rate, average dry weight, and protein content of BSFL by 5%, 0.13 g/pc, and 8%, respectively. Then, we assessed the effect of 10B on the microbial community composition in the gut and frass of BSFL by Illumina Miseq sequencing. It shows that 10B can significantly alter microbial composition of gut while it did not cause a huge change in microbial composition of frass. Pearson's correlation analysis further showed that the Bacillus, unclassified_f_Caloramatoraceae, and Gracilibacillus were positively correlated with the survival rate, crude protein content, and substrate conversion rate of BSFL. To further investigate the effect of 10B on host metabolism, metabolic analyses on germ-free BSFL, monobacterial intestinal BSFL, and natural BSFL were also performed. The results proved that (i) 10B played a vital role in the survival of BSFL; ii) 10B regulated the amino acid synthetic and metabolic process of BSFL, thus leading to the rise of protein content of BSFL. In addition, vitamins backfill assay verified that the BSFL survival rate was significantly improved by supplying the germ-free BSFL with riboflavin, which further suggests that 10B determines the survival of BSFL via delivering riboflavin. Overall, this study provides a reference for understanding the comprehensive contribution of a specific probiotic to its host.